TANTANGAN MENGHADAPI GLOBALISASI: BELAJAR DARI BEBERAPA NEGARA - Indra Pahlevi (Jurnal Politica, 2012)
Current world economy is entering a new phase of crisis after it has begun in Europe. Nevertheless, this time the crisis is not as bad as the Asian crisis emerged in late 1990s. It is argued here that the crisis is an impact of unstopped waves of globalization and liberalism across the world in the last century. It is then questioned by the writer how is the role of state as a regulating power in controlling that phenomenon. Aside from the reality that globalization cannot be stopped, the writer says that there is a need to safeguard and revive the notion of nationalism in order to limit the impact. The writer draws attention to learn from of countries’ experience such as India, China, Korea, and Taiwan in coping with the issues of globalization, liberalism, and its impact. Indonesia can take good lessons from those countries without totally following their paths due to the reason hat every country has their own background or history, meaning that the crisis solution is not always the same.